2018
DOI: 10.1038/s41598-018-29619-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of ticagrelor in patients with acute coronary syndromes

Abstract: Ticagrelor is a state-of-the-art antiplatelet agent used for the treatment of patients with acute coronary syndromes (ACS). Unlike remaining oral P2Y12 receptor inhibitors ticagrelor does not require metabolic activation to exert its antiplatelet action. Still, ticagrelor is extensively metabolized by hepatic CYP3A enzymes, and AR-C124910XX is its only active metabolite. A post hoc analysis of patient-level (n = 117) pharmacokinetic data pooled from two prospective studies was performed to identify clinical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
0
17
2
Order By: Relevance
“…As compared with swallowing ticagrelor, crushed ticagrelor tablets in the semi-upright sitting position [16,17] or [18,19] also accelerate platelet inhibition. Except for drug interactions, a previous study revealed that smoking appears to increase the degree of ticagrelor transformation in patients with ACS [20]. On the contrary, our results pointed out no differences in AUC 0-12 ratio between AR-C124910XX and ticagrelor for smokers and non-smokers.…”
Section: Discussioncontrasting
confidence: 79%
“…As compared with swallowing ticagrelor, crushed ticagrelor tablets in the semi-upright sitting position [16,17] or [18,19] also accelerate platelet inhibition. Except for drug interactions, a previous study revealed that smoking appears to increase the degree of ticagrelor transformation in patients with ACS [20]. On the contrary, our results pointed out no differences in AUC 0-12 ratio between AR-C124910XX and ticagrelor for smokers and non-smokers.…”
Section: Discussioncontrasting
confidence: 79%
“…Moreover, presence of different AR-C124910XX formation rates between compared groups suggests potential diversity in drug metabolism and/or elimination. Recently, it has been reported that the presence of STEMI and diabetes are connected with impaired metabolism of ticagrelor during the first 6 h after ticagrelor LD for acute coronary syndrome [26]. In the current trial clear differences were observed in ticagrelor's active metabolite formation between patients with and without OHCA treated with MTH, however small the size of cardiac arrest, the survivor group did not allow formal conclusions to be drawn.…”
Section: Discussioncontrasting
confidence: 58%
“…In a subsequent analysis, it has been reported that the main determinants of HTPR at 1 and 2 h after ticagrelor loading dose are presence of STEMI and morphine co-administration (66). Furthermore, the presence of STEMI and diabetes mellitus were found to be associated with impaired metabolism of ticagrelor within first 6 h post ticagrelor loading dose in ACS patients (67). It has been recently published, that bioavailability of ticagrelor in MI patients managed with mild therapeutic hypothermia after out-of-hospital cardiac arrest is significantly decreased, thus increasing the risk of stent thrombosis, a possibly lethal complication, which is not uncommon in this specific subset of patients (68, 69).…”
Section: Assessment Of Platelet Inhibition Under Antiplatelet Therapiesmentioning
confidence: 99%